PENGEMBANGAN PENDIDIKAN ASWAJA SEBAGAI STRATEGI DERADIKALISASI - Naim, Ngainun (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2015)
This study discussed about the role of Aswaja lesson in the efforts of de-radicalization. Radicalization had been more and more evolved since after the fall of New Order. Reformation Era opened wide varieties of expression, included religious expression. The development of radicalization led to widespread of social unrest. Responses appeared, included using the counter-ideology. Aswaja was believed as being able to prevent the proliferation of radicalization. The data presented in this article was derived from observation, interview and review of the literature related to the topic of writing. The argument developed in this paper is that the reconstruction and actualization of the values contained in Aswaja might be personally internalized firmly. An important strategy that might be applyed to disseminate and internalize Aswaja is through education. In the schools in which applying Aswaja lesson, students had the opportunity to have a moderate religious understanding and avoid radicalization.***Penelitian ini mengulas tentang peranan pelajaran Aswaja dalam usaha deradikalisasi. Radikalisasi semakin berkembang pasca jatuhnya Orde Baru. Era Reformasi membuka lebar berbagai bentuk ekspresi, termasuk ekspresi keberagamaan. Semakin berkembangnya radikalisasi memunculkan keresahan masyarakat secara luas. Berbagai respons pun muncul, di antaranya melalui counter-ideologi. Aswaja diyakini dapat mencegah tumbuh suburnya radikalisasi. Data yang disajikan dalam artikel ini berasal dari observasi, wawancara dan telaah literatur yang berkaitan dengan topik tulisan. Argumen yang dibangun dalam tulisan ini adalah rekonstruksi dan aktualisasi nilai-nilai yang terkandung di dalam Aswaja dapat terinternalisasi secara kokoh dalam diri seseorang. Strategi penting yang dapat ditempuh untuk sosialisasi dan internalisasi Aswaja adalah melalui jalur pendidikan. Di sekolah-sekolah yang mengaplikasi mata pelajaran Aswaja, para siswanya memiliki peluang untuk memiliki pemahaman keagamaan yang moderat dan terhindar dari arus radikalisasi.